Between-session reliability of strength- and power-related variables obtained during isometric leg press and countermovement jump in elite female ice hockey players - Petré, H.; Psilander, N.; Rosdahl, H. (Sports, 2023)
Isometric leg press (ILP) and countermovement jump (CMJ) are commonly used to obtain strength- and power-related variables with important implications for health maintenance and sports performance. To enable the identification of true changes in performance with these measurements, the reliability must be known. This study evaluates the between-session reliability of strength- and power-related measures obtained from ILP and CMJ. Thirteen female elite ice hockey players (21.5 ± 5.1 years; 66.3 ± 8.0 kg) performed three maximal ILPs and CMJs on two different occasions. Variables from the ILP (peak force and peak rate of force development) and CMJ (peak power, peak force, peak velocity, and peak jump height) were obtained. The results were reported using the best trial, an average of the two best trials, or an average of three trials. The intraclass correlation coefficient (ICC) and coefficient of variation (CV) were high (ICC > 0.97; CV < 5.2%) for all outcomes. The CV for the CMJ (1.5-3.2%) was lower than that for the ILP (3.4-5.2%). There were no differences between reporting the best trial, an average of the two best trials, or an average of the three trials for the outcomes. ILP and CMJ are highly reliable when examining strength- and power-related variables in elite female ice hockey players.